Research on the influence of a high proportion of wind power connected to the receiving power grid on the system power angle stability - Deyang, Chen; Zixi, Lang; Yu, Liu; Jinchang, Chen; Zhennan, Yang; Zhigang, Wu; Chuyue, Chen (Frontiers in Energy Research, 2023)
With the increasing proportion of wind power integration, the effect on the stability of system power angle cannot be ignored. In this paper, based on the different power characteristics of direct-drive wind generators before and after a fault, the system model of the receiving-end grid with thermal units replaced by wind turbines is simplified. The influence of the increase of the replacement ratio of wind power in the receiving-end grid on the transfer impedance between the sending-end and receiving-end is analyzed. Based on the equal area rule, the influence of the replacement ratio k within the receiving-end grid, power grid operation mode and wind power integration point on the system power angle stability is analyzed. It is concluded that the stability of the system's power angle will first get better and then deteriorate with the increase of the replacement ratio of wind power, the system can bear a larger proportion of wind turbines under the low load operation mode, and the system's power angle of the replacement of wind power with equal capacity in the load center region is relatively better. Above conclusions are verified by simulation with real data of a bulk power system in China.